A study on correlation between arthroscopy and MRI in internal derangement of knee - Nippuleti, Anoop; Rudraraju, Raviteja; Dasari, Srivanth; Baig, Mirza Shahrukh (International Journal of Research in Orthopaedics, 2018)
Background: The knee joint is a common site of injury, mainly due to trauma, repetitive activities and sports activities. Multiple imaging modalities are currently used to evaluate pathologic conditions of the knee. Magnetic resonance imaging has a better soft tissue contrast and multi planar slice capability, which has revolutionized and has become the ideal modality for imaging complex anatomy of the knee joint. Another advanced modality in the management of IDK is arthroscopy, which can be used in its dual mode, either as diagnostic and/or as therapeutic tool. Methods: Cases were taken according to inclusion and exclusion criteria i.e., patients with knee problems more than 6weeks old, with symptoms of locking of knee, patients with undiagnosed knee pain and knee injury. Only patients between 15-50 years are included in the study. Patients with signs of infection, with osteoarthritis, ankylosis, and patients on ATT were excluded from the study. Results: In our study of 25 cases, there were 20 male and 5 female patients with age ranging from 15 years to 50 years with most patients in between 21-30 years. 11 cases admitted were sport injuries, 14 had motor vehicle accidents. Right side being more common side affected. Conclusions: In conclusion the present study supports that clinical diagnosis is of primary necessity and MRI is additional diagnosing tool for IDK.